Struktur Komunitas Odonata di Kawasan Wana Wisata Curug Semirang Kecamatan Ungaran Barat, Semarang - Irawan, Frendi; Hadi, Mochamad; Tarwotjo, Udi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Dragonflies role as a predator in an ecosystem and become a healthy aquatic bio-indicators related to the life cycle. The diversity of habitat, food and predators affect community structure dragonfly. This study aims to determine the composition and community structure dragonfly morning and afternoon as well as the relationship with the physical environmental factors on four habitat in Semirang waterfall. Research using transect Point Count method. Statistically, the biodiversity of odonata in each habitat is significantly different. The results shows there are 15 species from 10 Family in morning observations and 12 species of 6 Family in afternoon observations, with a total of 17 species of 10 family of odonata. Biodiversity in each station is low to moderately with high evenness. The highest abundance found in river habitat without the canopy during the afternoon that Vestalis luctuosa (61.29%), while the lowest abundance found in the the canopied river habitat when afternoon that is Drepanosticta spatulifera (1.33%). Common species at area of Semirang waterfall are Euphaea variegata, Orthetrum sabina and Vestalis luctuosa. Endemic species at area of Semirang waterfall are Heliocypha fenestrata, Drepanosticta spatulifera and D. sundana.Â Key words : Community structure, Odonata, Semirang waterfall